PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI UPTD SD NEGERI 122384 - Simanjuntak, Melvin; Esti Marlina Sirait; Cintami Elisabet Situmorang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the effect of the Example Non Example learning model on students’ learning outcomes in Grade V at UPTD SD Negeri 122384 Pematangsiantar in the 2025/2026 academic year. The research approach used is quantitative with a Pre-Experimental design, specifically the One Group Pretest-Posttest Design. The research sample consisted of all 20 Grade V students of UPTD SD Negeri 122384 Pematangsiantar. Data were collected through a multiple-choice test consisting of 20 items, which had previously undergone validation, reliability testing, item discrimination analysis, and difficulty level assessment. The data were analyzed using the score improvement test (N-Gain).The results showed that the students’ average pretest score was 45.5 with a mastery level of 10%, which then increased to 87 with a mastery level of 90% in the posttest. The average N-Gain score of 0.7831 indicated a high improvement category, with a learning effectiveness of 78.31%. These findings indicate that the Example Non Example learning model had a significant effect on the learning outcomes of Grade V students in Pancasila Education.